Hospitality students’ satisfaction with industrial internship program: The influence of perceived supports - Mohd Aliff Abdul Majid; Ana Batrisyia Azman; Siti Nor Bayaah Ahmad; Agus Riyadi; Mohd Nazri Abdul Raji (Academic Science Publications and Distributions, 2025)
Internships play a pivotal role in enhancing the employability of graduates by providing essential skills and knowledge for career advancement. It is crucial to understand students' perspectives on internships and evaluate their satisfaction levels with the internship experience, as satisfaction directly influences hospitality undergraduates' decisions about their future in the industry. This research aims to investigate the influence of perceived organizational support, perceived supervisor support, and perceived co-worker support on internship satisfaction among hospitality students. A quantitative, correlational research approach consisting of a closed-ended structured questionnaire was employed. The numerical data were collected through an online survey via convenience sampling. A total of 101 valid responses were analyzed using SEM-PLS. The findings highlight the significance of perceived supervisor support as the primary influencer of internship satisfaction. Specifically, the quality of guidance, feedback, and mentorship provided by supervisors significantly shapes students' overall evaluation of their internship. Besides, this research contributes to a deeper understanding of internship satisfaction in both academia and industry, particularly emphasizing the important role of supervisor support in shaping positive internship experiences. These findings have implications for hospitality programs in designing and managing internship programs, highlighting the need for structured supervisor training and development. Furthermore, organizations within the hospitality sector can utilize these insights to enhance their internship programs, thereby improving intern satisfaction and potentially increasing the likelihood of attracting and retaining future talent. Hence, future research could explore the long-term impact of internship satisfaction on career choices and performance.